2018
DOI: 10.1007/s10676-018-9449-5
|View full text |Cite
|
Sign up to set email alerts
|

The virtual simulation of child sexual abuse: online gameworld users’ views, understanding and responses to sexual ageplay

Abstract: This paper explores cultural understandings of virtual sexual ageplay in the online world of Second Life. Online sexual ageplay is the virtual simulation of child abuse by consensual adults operating in-world with child computer characters (avatars). Second Life is primarily governed by Community Standards which rely on residents (the users of Second Life) to recognise sexual ageplay and report it, which requires an appreciation of how residents view, understand and construct sexual ageplay. The research prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Interestingly, experiments have shown that virtual touch of the avatar body one is wearing is related to erotic experiences (Mello et al, 2021). Non-consensual practices, such as virtual rape or sexual interactions with avatars that look like children, are also known and have been met with vivid discussions in the research community regarding their ethical and legal implications (Strikwerda, 2015;Reeves, 2018). New emerging technologies, such as augmented reality (AR), become more and more widespread.…”
Section: Technology-mediated Sexual Interactions Via Immersive Virtual Environmentsmentioning
confidence: 99%
“…Interestingly, experiments have shown that virtual touch of the avatar body one is wearing is related to erotic experiences (Mello et al, 2021). Non-consensual practices, such as virtual rape or sexual interactions with avatars that look like children, are also known and have been met with vivid discussions in the research community regarding their ethical and legal implications (Strikwerda, 2015;Reeves, 2018). New emerging technologies, such as augmented reality (AR), become more and more widespread.…”
Section: Technology-mediated Sexual Interactions Via Immersive Virtual Environmentsmentioning
confidence: 99%
“…What is noteworthy about them, however, is that most contributors to the debate accept the starting position that representing and engaging in acts of virtual child sexual abuse is immoral. This stance is backed up by studies of users of virtual social platforms such as Second Life, who generally see sexual 'ageplay' (when adult users of the platform play at being children engaging in sexual acts) as something that transgresses or lies at the extreme edge of what is acceptable on the platform (Reeves 2018). This supports the notion that there is something different about virtual sexual immorality in most people's minds.…”
Section: Could Something Similar Not Be True Of Actions In Virtual En...mentioning
confidence: 84%